Laughing Matter(s): Reactions of Muslims in Europe to Islamophobia and the Role of Comic Relief - Aydin, Zeynep (Journal of Muslims in Europe, 2023)
Laughter and humour can have therapeutic effects on traumatized individuals. Now, the generation of Muslims that grew up after the 9/11 terror attacks is using comic relief to recount their experience with Islamophobia. While the trend started with television stand-up comedians and their performances, the movement has spread through the social media grape vine all the way from Twitter to TikTok. In this article the (social) media landscape is examined and comedic content is analysed to assess how and why content creators share their experiences. It finds that the greatest difference between content creators results from the gender-based experiences they draw on when recounting their stories. Comedy was a very strong means of communicating this highly sensitive subject. Through humour, content creators also wished to also break the stereotype of Muslims not understanding satire and just being an angry inflexible mob.